Synthesis, Characterization, in silico and in vitro Studies of Transition Metal Complexes with Biologically Active Ligand as Antigout Agent Colchicine (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Colchicine is essentially useful in the treatment of gout. In the present work Colchicine Complexes has been prepared with transition metals viz; Copper(II) [Cu(II)], Zinc (II) [Zn(II)], Cobalt (II) [Co(II)], Nickel (II) [Ni(II)] and those checked for molecular docking, it has been observed that Zn(II) and Ni(II) complex has revealed good binding energy than the parent ligand, the increased binding energy of colchicine metal complexes indicates that, the tubulin polymerization inhibitor tendency is enhanced, consequently antigout property is also increased. As transition metals have antimicrobial activity in themselves, complexes are also characterized for the antimicrobial activity which is enhanced for Cu(II) and Co(II) metals.